2020
DOI: 10.1007/s00421-020-04399-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing bilateral deficit and inter-limb asymmetry of maximal and explosive strength: motor task, outcome measure and muscle group

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 33 publications
5
30
2
2
Order By: Relevance
“…Compared to local peak torque asymmetries, rate of torque development showed to be a more sensitive parameter for assessment of asymmetries. That is in accordance with findings of Sarabon et al [23], who reported that the RTD showed larger magnitudes of asymmetries than peak torque during unilateral isometric knee flexion and extension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared to local peak torque asymmetries, rate of torque development showed to be a more sensitive parameter for assessment of asymmetries. That is in accordance with findings of Sarabon et al [23], who reported that the RTD showed larger magnitudes of asymmetries than peak torque during unilateral isometric knee flexion and extension.…”
Section: Discussionsupporting
confidence: 93%
“…The reason for inconsistent findings could lay in discrepancies among populations, methods of asymmetry calculation, and COD tests, as well as in low asymmetry values, that are not large enough to influence performance. Taking that into consideration, Sarabon et al [23] found that explosive strength parameters like rate of torque development (RTD) are more sensitive to detect inter-limb asymmetries compared to maximal strength outcomes like peak force or peak torque during maximal voluntary contractions (MVC), which were used in previous research. Also, local inter-limb asymmetries were assessed only for the knee joint, while proximal regions of hip and trunk were overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetry in force generation has been more studied in sports populations, probably because of the relationship between asymmetry and sports performance and injury risk [53]. In the physically active or athletic population the degree of isokinetic asymmetry of knee extensors was 3.7%, according to a meta-analysis of seven studies with a total sample of 173 participants [54], and in 259 athletes the average asymmetry in MVIC was 9% [55]. Asymmetry increases significantly after an injury or surgery on the locomotive system and afterwards tends to decrease with physical reconditioning [51].…”
Section: Discussionmentioning
confidence: 99%
“…Dedicated longitudinal studies are required to use a data-driven approach to determine which muscle groups provide complementary information in addition to quadriceps strength monitoring. An important aspect to consider is the current transition to home-based assessments (i.e., remote monitoring); [23][24][25][26] portability, cost-effectiveness and the potential for unsupervised, userfriendly assessments should have a prominent place in any future iteration of the PFD.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing examiner variability may, therefore, significantly reduce measurement error and optimize the sensitivity of muscle strength testing in MND. Fixed dynamometry (i.e., fixation of the dynamometer in a rigid structure) has been shown to alleviate the limitations of the HHD, but currently available systems still require a trained examiner and hospital visits [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%